Carbon availability and soil moisture drive the Arctic soil methane sink (Nature climate change, 2023)
Arctic uplands consume atmospheric methane, but whereas methane emissions are reasonably well studied, Arctic soil methane uptake is poorly understood. High-resolution measurements show that the Arctic soil methane sink might currently be underestimated, and is driven by soil moisture and labile carbon availability, implying increased methane uptake with climate change.